A review of informed consent and how it has evolved to protect vulnerable participants in emergency care research. Issue 2 (3rd February 2020) - Nandra, Rajpal; Brockie, Alan F.; Hussain, Faisal
Abstract : A vulnerable participant in research lacks capacity to consent or may be exposed to coercion to participate. Capacity may be temporarily impaired due to loss of consciousness, hypoxia, pain and the consumption of alcohol or elicit substances. To advance emergency care, providing life-threatening measures in life-threatening circumstances, vulnerable patients are recruited into research studies. The urgent need for time-critical treatment conflicts with routine informed consent procedures. This article reviews ethical considerations and moral obligations to safeguard these participants and preserve their autonomy. A particular focus is given to research methodology to waive consent, and the role of ethics committees, research audits, research nurses and community engagement. Research on the acutely unwell patient who lacks capacity is possible with well-designed research trials that are led by investigators who are sufficiently trained, engage the community, gain ethical approval to waive consent and continuously audit practice. Cite this article: EFORT Open Rev 2020;5:73-79. DOI: 10.1302/2058-5241.5.180051